Statin-associated myopathy: a general overview - Harfoush, Allam (The European Research Journal, 2019)
Among the amazing turn of events in preventing and reducing the risk of cardiovascular diseases since the discovery of statins, thousand of physicians started to prescribe it as a regular life-long treatment, but regarding the expanding number of patients on statin therapy, a wide spectrum of side effects started to appear. Statin-associated myopathy considered as one of the most common side effects and could be subtle for a long time, we performed a review to provide a clinical summary of statin-associated myopathy and to discuss possible mechanisms of risk factors and management of statin-associated myopathy.